THE ROLE OF MYTH IN THE EMERGANCE OF EYE AS A SYMBOL FOR THE ANCIENT EGYPTIAN - Dr.Tatheer Abdul Jabbar Naji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The eye played a part in the hieroglyphic language when it appeared as one of the signs or symbols that expressed the activities and actions related to them, such as vision, attention, observation, etc. So, it was chosen as a mythical symbol due to its importance as an organ of the human body and as a main focus of the conflict between Horus and Seth. The eye was called "Alwchaat", the left eye of the God of Horus, which he lost in his eternal struggle with his maleficent enemy, Set. Its completion indicates health and strength. It is a graphic translation for Egyptian ancient Math in which it is regarded as an arithmetic equivalent for the parts of the even one. It was used in amulets and necklaces for protecting and preserving in which it was in the form of the cobra snake, which protects from harm on the forehead of the god, and it is one of the most common and strangest symbols in Egyptian art.